Pertanggungjawaban Notaris Atas Pembuatan Akta Pendirian Perseroan Terbatas yang Dibuat Berdasarkan Dokumen Palsu - Sidabukke, Sahat Marulitua; Josa, Meidia (Notary Journal, 2025)
In establishing an LLC, the notary oversees the establishment of the company starting from the preparation and drafting of the deed of establishment of the LLC, ratification of the deed of establishment by the Ministry of Law and Human Rights, preparation of the company's articles of association, and checking documents. However, there have been cases in which the notary was negligent and did not apply the principle of caution in checking documents where the founder of the LLC authorized his assistant to provide fake documents before the notary to make the deed of establishment of the LLC. Furthermore, if a notary commits a violation and is found to have criminal elements, the Criminal Code regulates the punishment for the notary who violates the rules. The purpose of this research is to analyze the regulations regarding the accountability of notaries who establish LLC based on fake documents. The method used in this research is empirical normative method, using secondary data from various legal literature supported with results from interview. From the analysis carried out, it can be concluded that a notary who has proven to have committed an unlawful act can be subjected to Code of Ethics sanctions by the Honorary Council in the form of reprimand, warning of temporary dismissal from the organization, honorable dismissal from the organization, or dishonorable dismissal from the organization. Bahasa Indonesia Abstract: Dalam pendirian PT, notaris mengawal  pendirian  perseroan  mulai  dari  Penyusunan  dan  Pembuatan akta pendirian PT, Pengesahan akta pendirian oleh Kementerian Hukum dan HAM, Penyusunan anggaran dasar perusahaan, dan pengecekan dokumen. Namun ada kasus terjadi di mana notaris lalai dan tidak menerapkan prinsip kehati-hatian dalam melakukan pengecekan dokumen yang mana pendiri PT nya memberikan kuasa kepada asistennya untuk memberikan dokumen palsu di hadapan notaris untuk membuat akta pendirian PT. Lebih lanjut, jika notaris yang melakukan pelanggaran dan ditemui ada unsur-unsur pidananya maka KUHP yang mengatur hukuman untuk notaris yang melanggar aturan. Penelitian ini bertujuan untuk menganalisis pengaturan dalam pertanggungjawaban notaris yang melakukan pendirian PT berdasarkan dokumen palsu. Metode yang digunakan dalam penelitian ini adalah metode normatif empiris dengan menggunakan data sekunder dari berbagai literatur hukum yang didukung dengan hasil wawancara. Dari analisa yang dilakukan, dapat disimpulkan bahwa notaris yang terbukti melakukan suatu perbuatan melawan hukum dapat dikenakan sanksi Kode Etik oleh Dewan Kehormatan berupa teguran, peringatan pemberhentian sementara dari organisasi, pemberhentian dengan hormat dari organisasi, atau pemberhentian dengan tidak hormat dari organisasi.